2016
DOI: 10.5603/cj.a2015.0081
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction following transcatheter aortic valve implantation: Multiple risk scores comparison

Abstract: p = 0.59; EuroSCORE II, AUC 0.59; p = 0.23; STS, AUC 0.55; p = 0.52; ACEF, AUC 0.54; p = 0.69; Ambler's, AUC 0.54; p = 0.70; OBSERVANT, AUC 0.597; p = 0.21; SURTAVI, AUC 0.535; p = 0.65. SURTAVI model was calibrated best in high-risk patients showing coherence between expected and observed mortality (10.8% vs. 9.4%, p = 0.982). ACEF demonstrated best classification accuracy (17.5% vs. 6.9%, p = 0.053, respectively). Conclusions: None of the investigated risk scales proved to be optimal in predicting 30-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Furthermore, despite the logistic EuroSCORE and STS score did not differ between groups, the EuroSCORE II was significantly higher in Group B. As already reported in TAVI population, this discrepancy probably reflects the inability of these scores, designed and validated in patients candidate for surgery, to stratify prognosis in a high‐risk population …”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, despite the logistic EuroSCORE and STS score did not differ between groups, the EuroSCORE II was significantly higher in Group B. As already reported in TAVI population, this discrepancy probably reflects the inability of these scores, designed and validated in patients candidate for surgery, to stratify prognosis in a high‐risk population …”
Section: Discussionmentioning
confidence: 61%
“…Although these initial findings would suggest that the EuroSCORE II and STS Score may be superior to the LES, Wang et al further showed that the these surgical risk scores only weakly discriminated operative mortality after TAVR with a pooled c‐statistic of 0.62, limiting our ability to apply these scores to TAVR patients. Efforts to address this issue by designing TAVR‐specific risk models, 15–19 while promising, have not been shown to be superior to their surgical counterparts in external validation studies 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…Other scores, such as the OBSERVANT-score, 48 FRANCE-2 score, 49 the SURTAVI risk stratification model, 50 and the German Aortic Valve Score 51 have been developed to specifically assess mortality risk in patients undergoing TAVR (and SAVR), but have shown limited additional accuracy in predicting 30-day mortality in comparison with EuroSCORE and STS score in different datasets. 52,53 The impact of pre-procedural frailty on post-operative outcome after TAVR has been the subject of interest in TAVR research. Frailty is a state of decreased physiologic reserve, resulting in vulnerability when a stressor is applied.…”
Section: Advantages Of a Multidisciplinary Approach In Cardiac Diseasementioning
confidence: 99%